Factors associated with unfavorable outcomes in older patients with traumatic brain injury: analysis from the “All of Us” research program - Chen, Zhangying; Wang, Zihao; Mentis, Alexios-Fotios A.; Stey, Anne M.; Schwulst, Steven J. (Frontiers in Neurology, 2024)
Traumatic brain injury (TBI) afflicts approximately 70 million people worldwide annually, with patients aged 65 years and older accounting for an increasing proportion of TBI patients. Older patients also experience increased morbidity and mortality post-TBI compared to their younger counterparts. Nevertheless, clinical trials often exclude older TBI patients, and age-specific TBI treatment is lacking. We hypothesized that the APOE genotype and age-associated comorbidities, such as heart disease, are associated with unfavorable outcomes following TBI in older patients. We utilized a dataset from the “All of Us research” (AoU) to study this vulnerable population post-TBI. Launched by the National Institutes of Health (NIH), AoU is a nationwide prospective cohort study aiming to enroll 1 million or more individuals by emphasizing traditionally underrepresented populations in the United States. We defined patients diagnosed with post-concussion syndromes (PCS) as those with unfavorable TBI outcomes, and we also assessed the associations between PCS observed in older patients and different comorbidities variables/APOE genotypes via multiple logistic regression models. Consequently, APOE ε4 allele was strongly associated with PCS in patients aged 65 and older. Our findings provide direct evidence for developing better predictive tools and potentially improving the clinical guidance and management of older adults with TBI.